Dealing with Operational Mine Waste Closure Constraints Through an Integrated Rehabilitation Policy — A Platinum Mine Case - van Wyk, S.J.; Smit, P.J.L.; van der Merwe, M. (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
Mine waste stockpile facilities, including tailings dams, heap leach pads, rock dumps, slag dumps, open cast overburden and general waste disposal sites, are known to present, from an environmental perspective, the mining industry’s largest long-term surface liability. Focused management for closure during the life of a mine is widely acknowledged as the only means to cost-effectively minimize the impacts of these facilities on the surrounding environment during the life of a mine. Despite industry guidelines, scientific facility design, compliance with legislative processes and focused environmental management program (EMP) management, effective closure of these facilities still proves to be challenging. A review is presented, and a way forward for overcoming the operational constraints of concurrent mine waste facility rehabilitation is proposed. The operational challenges to mine closure are discussed, and an integrated policy model is proposed to deal with these challenges. Continuity of mine personnel, consultants, contractors and regulators, as well as poor aftercare regulation and limited budgets, are the main issues pertaining to operational mine waste facility closure constraints. One way to deal with these issues is to integrate closure practice during operations, which is driven by a closure policy, and followed through by strict operational procedures, continual monitoring, and sign-off of closed sites based on scientific information. This methodology also presents significant closure cost savings – doing it right the first time during the lowest financial risk period – and better closure liability estimates. The closure approach followed by LONMIN is a simple, yet effective way to deal with continuity, and sets high internal standards in the mine closure process.